Kebijakan Presiden Joko Widodo dalam Menanggulangi Terorisme - Mukhtar, Sidratahta (Pusat Kajian Keamanan Nasional (Puskamnas) Universitas Bhayangkara Jakarta Raya, 2021)
This paper discusses the government's response to the threat of terrorism in Indonesia. Several theoretical frameworks of policy theory, terrorism, and the sociology of religion are used to explain President Jokowi’s policy on radicalism/terrorism. This study found that Indonesia has a strong response in managing terrorism but it needs a new strategy and approach that focuses on a collaborative approach, as well as soft power and hard which is based on the principles of accountability, human rights, and democracy.